One Decade of Environmental Disasters in Brazil: The Action of Veterinary Rescue Teams - Carla Sássi; Gabriel Domingos Carvalho; Leonardo Maggio de Castro; Cláudio Zago Junior; Vânia de Fátima Plaza Nunes; Arthur Augusto Tavares do Nascimento; Ana Liz Ferreira Bastos; Ana Liz Ferreira Bastos; Luciana Guimarães Santana; Ilka do Nascimento Gonçalves (Frontiers Media S.A., 2021)
Based on the interdisciplinary concept of One Health, EcoHealth, and Planetary Health, this paper focuses on participatory knowledge-to-action approaches by relating one decade of environmental disasters in Brazil with the action of veterinary rescue teams, aiming to give support to future disaster preparedness. This paper will present the historic actions of teams rescuing animal that are victims of environmental disasters, in addition to addressing the need for contingency plans and response management in these types of events. The main events in Brazilian states where veterinary rescue teams participated were, chronologically, as follows: 2011 flood and landslide (Rio de Janeiro); 2012 flood (Acre, Minas Gerais, and Pará); 2015 dam break (Minas Gerais); 2017 flood (Minas Gerais) and forest fire (Minas Gerais and Goiás); 2019 dam break and evacuation (Minas Gerais) and flood (Bahia); 2020 flood (Espírito Santo and Minas Gerais) and forest fires (Mato Grosso and Mato Grosso do Sul). The Brazilian disasters that had a large global repercussion were the ruptures of the ore dams in Marina (2015) and Brumadinho (2019), both in the State of Minas Gerais. The role of veterinarians in these events was recognized by the Federal Council of Veterinary Medicine (CFMV) after their performance in Mariana, Minas Gerais (2015), and in 2020, the CFMV approved the National Mass Disaster Contingency Plan Involving Animals. The work of veterinarians in interaction with other professionals in environmental disasters proved to be effective and necessary for the rescue of animals and for planning and giving support to disaster preparedness in the future.